2010
DOI: 10.1080/00423110903540751
|View full text |Cite
|
Sign up to set email alerts
|

Development of a vehicle–track model assembly and numerical method for simulation of wheel–rail dynamic interaction due to unsupported sleepers

Abstract: 2010)Development of a vehicle-track model assembly and numerical method for simulation of wheel-rail dynamic interaction due to unsupported sleepers, Vehicle System Dynamics: International Journal of Vehicle Mechanics and Mobility, 48:12, 1535-1552 To link to this article: http://dx.In practice, it is not very uncommon to find railway track systems with unsupported sleepers due to the uneven settlement of a ballasted track system. These unsupported sleepers are among the major vibration excitations for a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…By contrast, their study also shows that local maxima could be observed in different configurations considering the number of hanging sleepers, vehicle speed and the height of gap configurations. In another study [7], by means of configuration, several scenarios for a one-sided partially unsupported sleepers was simulated and resulted in similar conclusions such that higher speed increase the contact force variations. They also show that the effect of triangular configuration, where three assumed voids are sequentially placed under left, right and then left rails, have no significant effect on the contact forces.…”
Section: Introductionmentioning
confidence: 81%
“…By contrast, their study also shows that local maxima could be observed in different configurations considering the number of hanging sleepers, vehicle speed and the height of gap configurations. In another study [7], by means of configuration, several scenarios for a one-sided partially unsupported sleepers was simulated and resulted in similar conclusions such that higher speed increase the contact force variations. They also show that the effect of triangular configuration, where three assumed voids are sequentially placed under left, right and then left rails, have no significant effect on the contact forces.…”
Section: Introductionmentioning
confidence: 81%
“…Kaewunruen and Remennikov [8] conducted several laboratory studies on the effect of unsupported sleepers on modal analysis and consequences of vibration modes on the track. Zhu et al [9] investigated the effect of vehicle speed, gap size and the number of unsupported sleepers by assuming a continuous track system model and an adaptive wheel-rail contact model. Rezaei and Dahlberg [10] by presenting their cross-section model of track, showed that the effect of pad stiffness is negligible on sleeper dominant frequency and the effective parameters are sleepers flexural stiffness, mass, and its distribution .…”
Section: Literature Reviewmentioning
confidence: 99%
“…(21). Considering the last wheel crossing the track, the calculating time can (9) be computed through Eq. (22), where l0 is the rigid wheelbase of the wagon and l is the length of the selected track.…”
Section: The Inputsmentioning
confidence: 99%
“…6-The fundamentals of derailment are based on the Nadal formula which is an international formula. The equation of this theory is (Iwnicki, 1998 andZhu et al, 2010):…”
Section: Dynamic Analysis Assumptions and Basicsmentioning
confidence: 99%